2009
DOI: 10.1111/j.1365-2133.2009.09562.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical photodynamic therapy is immunosuppressive in humans

Abstract: Topical PDT induced significant immune suppression, which could impair local antitumour immune responses and may thus contribute to treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 26 publications
4
38
0
3
Order By: Relevance
“…Using this model, we recently reported that topical ALA/MAL-PDT, delivered at 78 mW cm À2 , is highly immunosuppressive in humans (Matthews and Damian, 2010). We now report that ALA/MAL-PDT at high but not low-fluence rates is immunosuppressive and causes generation of 8oxoG lesions in humans.…”
Section: Introductionmentioning
confidence: 75%
“…Using this model, we recently reported that topical ALA/MAL-PDT, delivered at 78 mW cm À2 , is highly immunosuppressive in humans (Matthews and Damian, 2010). We now report that ALA/MAL-PDT at high but not low-fluence rates is immunosuppressive and causes generation of 8oxoG lesions in humans.…”
Section: Introductionmentioning
confidence: 75%
“…[29] Yet, there is growing evidence that ALA-induced PDT can act as a biological response modifier. Both innate and adaptive immune responses contribute to tumor apoptosis, as described later [42][43][44][45].…”
Section: Biological Activity Of Heme and Its Metabolitesmentioning
confidence: 99%
“…Известны феномены подавления активации Т-лимфоцитов после ФДТ, удлинение времени приживления кожного трансплантата и другие иммуносупрес-сорные проявления [47].…”
Section: Introductionunclassified
“…афферентного иммунного ответа), которая включает в себя применение кожной ап-пликации гаптена, с последующим повторением [48], и подавление реакции гиперчувствитель-ности замедленного типа (на примере Манту) (т.е. эфферентной иммунный ответ), например, у здоровых Манту-положительных добровольцев [47,57]. В частности, такие иммуносупрессивные ответы, как представляется, зависят от скорости доставки света [26] и анатомических особенно-стей области ФДТ [49].…”
Section: Introductionunclassified